2011
DOI: 10.1115/1.4003826
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Study and Compare the Annual Performance of Liquid and Solid Desiccant Cooling Systems

Abstract: Desiccant cooling systems, considered one of the sustainable air conditioning technologies, have been attractive for researchers to be studied for many years. In this paper, the modeling and simulation of a packed tower liquid dehumidifier and regenerator as well as a solid desiccant wheel are presented. The simplified equations that predict the air conditions after passing these systems are developed. This approach is quick and does not need a lengthy computer calculation and large memory capacity. Liquid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…They also concluded that the temperature and flow rates of cooling and heating water and the flow rates of the solution through the absorber and regenerator affect the humidity level of the conditioned space. Nia et al [4] adopted a new approach to study and compare between solid and liquid desiccant cooling systems and concluded that liquid desiccant systems are relatively large without technology improvements, but have lower COP with low capacities on comparison to solid desiccant systems. Mei and Dai [5] reviewed on liquid desiccant dehumidification for air-conditioning applications and concluded that liquid desiccants and easily grasp the humidity ratio, independent control and temperature although they have drawbacks of unstable operation and large dimension.…”
Section: Introductionmentioning
confidence: 99%
“…They also concluded that the temperature and flow rates of cooling and heating water and the flow rates of the solution through the absorber and regenerator affect the humidity level of the conditioned space. Nia et al [4] adopted a new approach to study and compare between solid and liquid desiccant cooling systems and concluded that liquid desiccant systems are relatively large without technology improvements, but have lower COP with low capacities on comparison to solid desiccant systems. Mei and Dai [5] reviewed on liquid desiccant dehumidification for air-conditioning applications and concluded that liquid desiccants and easily grasp the humidity ratio, independent control and temperature although they have drawbacks of unstable operation and large dimension.…”
Section: Introductionmentioning
confidence: 99%